L’intersectionnalité - Université du Québec en Abitibi-Témiscamingue (2020)
L’intersectionnalité
Keywords: approches et analyses; cours; intersectionnalité; pol5480; premier cycle; pédagogie; ressource en ligne; thématiques

Kiffe ta race - Binge Audio - Ly, Grace; Diallo, Rokhaya (Kiffe ta race - Binge Audio, 2018)
Pourquoi le mot « race » est-il tabou ? Qu’en est-il quand on est, à la fois, victime de discriminations raciales et sexuelles ? Comment assumer son identité plurielle ? Un mardi sur deux, Rokhaya Diallo et Grace Ly reçoivent un·e invité·e pour explorer les questions raciales sur le mode de la conversation et du vécu.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afro-féminisme; approches et analyses; care; com5170; communication; corps; cours; discipline; europe; france; identités; intersectionnalité; journalisme; justice sociale; militance; premier cycle; pédagogie; périodes historiques; racisme; régions géographiques; système colonial; systèmes d'oppressions; thématiques; théorie critique de la race; violences

Le positionnement intersectionnel comme pratique de recherche: faire avec les dynamiques de pouvoir entre femmes - Marcillat, Audrey; Miramond, Estelle; Rupert, Nouri; Çıngı Kocadost, Fatma (Les cahiers du CEDREF, 2017)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; cours; discipline; intersectionnalité; inégalités; militance; premier cycle; pédagogie; périodes historiques; régions géographiques; sciences humaines; sexisme; soc3113; sociologie; systèmes d'oppressions; thématiques; états-unis

Whose Culture Has Capital? A Critical Race Theory Discussion of Community Cultural Wealth - Yosso, Tara J. (Race, Ethnicity and Education, 2005)
This article conceptualizes community cultural wealth as a critical race theory (CRT) challenge to traditional interpretations of cultural capital. CRT shifts the research lens away from a deficit view of Communities of Color as places full of cultural poverty disadvantages, and instead focuses on and learns from the array of cultural knowledge, skills, abilities and contacts possessed by socially marginalized groups that often go unrecognized and unacknowledged. Various forms of capital nurtured through cultural wealth include aspirational, navigational, social, linguistic, familial and resistant capital. These forms of capital draw on the knowledges Students of Color bring with them from their homes and communities into the classroom. This CRT approach to education involves a commitment to develop schools that acknowledge the multiple strengths of Communities of Color in order to serve a larger purpose of struggle toward social and racial justice.
Keywords: approches et analyses; cours; discipline; histoire et politique; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; sciences de l'éducation; sex2283; thématiques; théorie critique de la race

Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences